A Biomechanical Analysis of Muscle Force Changes After Bilateral Sagittal Split Osteotomy - Pachnicz, Dominik; Stróżyk, Przemysław (Frontiers in Physiology, 2021)
A basic procedure affecting maxillofacial geometry is the bilateral sagittal split osteotomy. During the surgery, the bony segments are placed in a new position that provides the correct occlusion. Changes in the geometry of the mandible will affect the surrounding structures and will have a significant impact on the functioning of the masticatory system. As a result of the displacement of the bone segment, the biomechanical conditions change, i.e., the load and the position of the muscles. The primary aim of this study was to determine the changes in the values of the muscular forces caused by mandible geometry alteration. The study considered the translation and rotation of the distal segment, as well as rotations of the proximal segments in three axes. Calculations were performed for the unilateral, static loading of a model based on rigid body mechanics. Muscles were modeled as spring elements, and a novel approach was used to determine muscle stiffness. In addition, an attempt was made, based on the results obtained for single displacements separately, to determine the changes in muscle forces for geometries with complex displacements. Based on the analysis of the results, it was shown that changes in the geometry of the mandibular bone associated with the bilateral sagittal split osteotomy will have a significant effect on the values of the masticatory muscle forces. Displacement of the distal segment has the greatest effect from −21.69 to 26.11%, while the proximal segment rotations affected muscle force values to a less extent, rarely exceeding 1%. For Yaw and Pitch rotations, the opposite effect of changes within one muscle is noticed. Changes in muscle forces for complex geometry changes can be determined with a high degree of accuracy by the appropriate summation of results obtained for simple cases.